2018
DOI: 10.24843/pjiib.2018.v18.i01.p04
|View full text |Cite
|
Sign up to set email alerts
|

Contact Phonology : Fonologi Kata Serapan dalam Bahasa Jepang

Abstract: This paper focuses its discussion about loanword phonology in Japanese language. Loanword phonology is one of five contact phonology situations that was described by Smith (2007). The four other situations are areal influence, dialect mixing, language mixing, and simplification. Japanese language has been borrowing many words from foreign languages. One of those foreign languages is English. As we all know that both languages, Japanese and English, have different phonological system. Therefore, borrowed words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Based on the three types above, it can be concluded that Japanese tend to change the vowels or consonants which are not present in Japanese phonological system to the closest sound of the English words. This result is similar to the study conducted by Oeinada (Oeinada, 2018) who also found that the adaptation of English loanwords in Japanese is based on the similarity of the closest sound of vowels and consonants in English as can be seen from one of his data below.…”
Section: Substitution From /L/ To /R/supporting
confidence: 90%
See 1 more Smart Citation
“…Based on the three types above, it can be concluded that Japanese tend to change the vowels or consonants which are not present in Japanese phonological system to the closest sound of the English words. This result is similar to the study conducted by Oeinada (Oeinada, 2018) who also found that the adaptation of English loanwords in Japanese is based on the similarity of the closest sound of vowels and consonants in English as can be seen from one of his data below.…”
Section: Substitution From /L/ To /R/supporting
confidence: 90%
“…Based on the rules above, it can be seen that in the process of substitution of /l/ to /r/, there are two processes, they are; deletion of /l/ sound and then the deleted sound is substituted by a new sound /r/. This result is a bit different from the one conducted by (Oeinada, 2018) who said that /l/ and /r/ in Japanese are not different, and they can be considered as allophones. In contrast, based on the data analysis, the writer assumed that /l/ and /r/ are different phoneme because in the distinctive features, there are two different features: [+/-ant] and [+/-lat].…”
Section: Stoppingmentioning
confidence: 96%